2018
DOI: 10.1002/1873-3468.13035
|View full text |Cite
|
Sign up to set email alerts
|

The antimalarial compound ELQ‐400 is an unusual inhibitor of the bc1 complex, targeting both Qo and Qi sites

Abstract: Edited by Peter BrzezinskiInhibitors of the mitochondrial respiratory chain cytochrome bc 1 complex, such as the antimalarial atovaquone and ELQ-300, and many well-studied compounds, are classified as either Q o or Q i site inhibitors based on their site of action. Here, we investigated the site of action of ELQ-400 that showed an unusual behaviour, being effective against parasites resistant to the Q o site inhibitor atovaquone or to the Q i site inhibitor ELQ-300. Analysis of yeast mutants and comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Based on previous results on ELQ efficacy against T. gondii and N. caninum (18,24), we also selected ELQ-316 and its prodrug ELQ-334, as well as ELQ-400, for further studies. ELQ-400 has been shown to exhibit outstanding in vivo activity, better than atovaquone, in an acute toxoplasmosis mouse model (22), and there is evidence that it acts as a dual Qo and Qi site inhibitor (21).…”
Section: Primary In Vitro Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous results on ELQ efficacy against T. gondii and N. caninum (18,24), we also selected ELQ-316 and its prodrug ELQ-334, as well as ELQ-400, for further studies. ELQ-400 has been shown to exhibit outstanding in vivo activity, better than atovaquone, in an acute toxoplasmosis mouse model (22), and there is evidence that it acts as a dual Qo and Qi site inhibitor (21).…”
Section: Primary In Vitro Screeningmentioning
confidence: 99%
“…Doggett et al (18) and Nilsen et al (19) reported the synthesis of novel endochin analogs with a diphenylether side chain at the third position, and various substitutions at the quinolone ring at position 5, 6, or 7. These include ELQ-300 and ELQ-316, which confer Qi site inhibition, and ELQ-400 (20), which has been reported to target both Qo and Qi sites of cytochrome b of S. cerevisiae and potentially other organisms (21). ELQ-316 inhibited T. gondii proliferation in vitro at sub-nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ELQ‐316 ( 623 ) has been shown to effectively inhibit the Q i subunit of cytochrome b in T. gondii . While not identified in the SAR studies, MMV671636 (ELQ‐400 624 ) was identified as an antiplasmodial uniquely capable of inhibiting both the Q 0 and Q i subunits of the cytochrome bc 1 complex, rendering it a particularly efficient inhibitor of respiration …”
Section: Filariasis and Wolbachiamentioning
confidence: 99%
“…However the inclusion of the additional 2‐(trifluoromethyl)pyridine resulted in a significant decrease in antiplasmodial activity . Diiodohydroxyquinoline ( 627 , MMV002817) also referred to as iodoquinol, is a poorly absorbed amoebicide, which chelates ferrous ions required for amoebic metabolism . While no link to filariasis or Wolbachia has been reported, it is possible that alteration of iron absorption may also influence cytochrome production.…”
Section: Filariasis and Wolbachiamentioning
confidence: 99%
“…Recently, McConnell et al studied the inhibitory effect of a library of ELQs on the cytochrome bc1 complexes of P. falciparum and T. gondii parasites, having concluded that, beside ELQ-271 and ELQ-316, the very promising candidate ELQ-400 (compound (e), Figure 1) was able to inhibit both the Qi and Qo sites, possibly due to the aforementioned structural flexibility, as well as the favorable substitution pattern [40,56]. In toxoplasmosis, this compound is thought to act on both acute and chronic stages, as demonstrated by the lack of parasites in the mice tissues, including the brain, suggesting an ability of the compound to cross the blood-brain barrier as well as a strong antiparasitic effect [40].…”
Section: Endochin-like Oxoquinolines (Elqs) and Quinoline-based Ppq-8mentioning
confidence: 99%